Review Of The Implementation Process Of Completion Of Juridical Code Violations Of Notary In Kendari - Hendro Kusuma Jaya Jaya; Amin Purnawan (Jurnal Akta, 2020)
Purposethis research are: 1)To identify and analyze judicial review implementation of the resolution process code violations notary in Kendari. 2) To identify and analyze the barriers and solutions implementation settlement process code violations notary in Kendari.The method used by researchers isempirical approach juridical law and specification in this study were included descriptive analysis. As for sources and types of data in this study are primary data obtained from field studies with interviews with the Honorary Board and Notary in Kendari. And secondary data obtained from the study of literature. Based on the results of research thatJudicial review implementation of Resolution Process Notary Code Violations In Kendari is a sanction that can be imposed by the Council of Honor of the Notary who proved to have violated the code of conduct in the form of a notary deed outside the office is layoffs. Obstacles in the process of settlement of violations of the code of ethics Notary in Kendari that the number of notaries who are numerous, with wide working area, the lack of awareness of the Notary to abide by a code of ethics, and supplies obtained Notary is not enough for his education, and still overlapping control regulations code conduct between the Honorary Board and the Supervisory Council of Notaries. Meanwhile, the Assembly secretariat Supervisory namely the unavailability of a representative, a lack of budgetary funds to conduct surveillance and optimal development, lack of attention / concern of government, and the lack of moral / Notary in running UUJN behavior and Notary Code. To provide a solution for the finalization of code violations Notary in Kendari, namely to provide guidance, supervision, guidance and counseling.Keywords : Judicial Review; Settlement; Breach; The Code; Notary.